The Effect of Asset Tangibility, Growth Opportunity, and Business Risk on Capital Structure in Retail Companies Listed on the Indonesian Stock Exchange from 2020-2024 - Yanufa Indah Rosyidatussa'idah; Risky Budianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the influence of asset tangibility, growth opportunities, and business risk on the capital structure of companies in the retail sector during the 2020–2024 period. A quantitative approach was employed, using secondary data in the form of financial reports from retail companies obtained from the Indonesia Stock Exchange website. The entire population comprised 47 retail companies in both the consumer cyclicals and non-cyclicals sectors. Purposive sampling resulted in 28 selected companies, bringing the total number of observations to 140 units over a five-year period. The analysis results indicate that asset tangibility alone does not influence capital structure, nor do growth opportunities or business risk. However, the combination of these three factors collectively contributes to capital structure.